Government Matters III : Governance Indicators for 1996-2002 - Kaufmann, Daniel; Kraay, Aart; Mastruzzi, Massimo (World Bank, Washington, DC, 2014)
The authors present estimates of six dimensions of governance covering 199 countries and territories for four time periods: 1996, 1998, 2000, and 2002. These indicators are based on several hundred individual variables measuring perceptions of governance, drawn from 25 separate data sources constructed by 18 different organizations. The authors assign these individual measures of governance to categories capturing key dimensions of governance and use an unobserved components model to construct six aggregate governance indicators in each of the four periods. They present the point estimates of the dimensions of governance as well as the margins of errors for each country for the four periods. The governance indicators reported here are an update and expansion of previous research work on indicators initiated in 1998 (Kaufmann, Kraay, and Zoido-Lobat 1999a,b and 2002). The authors also address various methodological issues, including the interpretation and use of the data given the estimated margins of errors.